2019
DOI: 10.1177/000313481908500234
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use is Associated with Increased Mechanical Ventilation and Polysubstance Use in Trauma Patients

Abstract: Recent policy changes in California regarding cannabis use underscore the need to study outcomes and prevalence of this drug in trauma. Our study aims to study the prevalence of cannabis use and associations with injury types and outcomes in Los Angeles County trauma patients. Data were reviewed from 21,276 adult patients from a Los Angeles countywide database spanning five years (2012–2016), who underwent urine toxicology testing in the ED after sustaining a traumatic injury. The percentage of trauma patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…THC + patients were more likely to be young males and were less likely to wear seatbelts, which is in agreement with the characteristics of THC + patients described in similar reports. 20 Overall, THC or any other positive toxicology was associated with an increased ISS compared with TOX–, although the odds of having an increased ISS was higher in the THC +ETOH patients than ETOH + patients for all ISS categories. This suggests that the combined use of alcohol and THC may have a synergistic effect on driver impairment, translating to worse injuries.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…THC + patients were more likely to be young males and were less likely to wear seatbelts, which is in agreement with the characteristics of THC + patients described in similar reports. 20 Overall, THC or any other positive toxicology was associated with an increased ISS compared with TOX–, although the odds of having an increased ISS was higher in the THC +ETOH patients than ETOH + patients for all ISS categories. This suggests that the combined use of alcohol and THC may have a synergistic effect on driver impairment, translating to worse injuries.…”
Section: Discussionmentioning
confidence: 84%
“… 19 Cannabis positivity in trauma patients has also been shown to be associated with increased hospital length of stay, intensive care unit days, ventilator days, and a greater number of operative interventions. 20 21 Conversely, studies by Movig and Longo reported that marijuana intoxication may not even be associated with an increased risk of motor vehicle crashes. 22 23 …”
Section: Introductionmentioning
confidence: 99%
“…There were 100 records that reported on the prevalence of AOD involvement in injury events. Of the 100 records that reported on all causes of injury (excluding transport events), 30 studies reported on the prevalence of AOD involvement in patients presenting to hospital after falls 24–52. One of these studies was excluded, since it reported exclusively on patients who denied consuming alcohol in the past year 38.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several papers examined overlapping datasets, including two studies each from the National Trauma Data Bank in the USA,27 44 the Oslo University Hospital Emergency Department,25 30 the R Adams Cowley Shock Trauma Centre24 48 and a trauma centre in Taiwan 32 45. Two papers obtained data from the Los Angeles County database, but used datasets with non-overlapping timeframes 26 49…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation